Metal fuel cells [Zn-air fuel cells]. - Riezenman, M.J.
The author describes a zinc-air fuel cell system which may be used for everything from electric vehicles (EVs) to backup generators, and may also provide practical and efficient energy storage
Keywords: Zn; Zn-air fuel cells; Backup generators; Electric vehicles; Electrochemical performance; Energy storage